Metode Pemahaman Hadits Menurut Muhammad Al-Ghazali, Yusuf al-Qardhawi, dan Yoseph Schacht - Nurdin Dihan; Rosalinda Rosalinda (Hikmah: Journal of Islamic Studies, 2018)
To explain of what is meant by the method in understanding the Hadith, it is important to begin this study to find out the foremost terms of method, and “Hadith semantically. A method is defined as “a well-ordered procedure and profoundly thinking to achieve its purpose (in science and et cetera). A systemic working procedure to simplify the implementation of an activity to achieve something has been determined. Therefore, the method in understanding Hadith is the procedures applied in understanding the Hadith. Many figures or scholars sincerely conduct researches on all of the existing Hadiths, both those are found in the Hadith books and those are not. Among many figures and Hadith scholars, both from Islamic world and “experts”, who sincerely studied the Hadith are from Orientalist (Western) circles. In this short article the author took only three Hadith figures for further study regarding to their method in understanding the Prophet’s Hadith. The three figures are Muhammad al-Ghazali, Yusuf al-Qardhawi, and Joseph Schacht. Keywords: Understanding of Hadith, al-Ghazali, al-Qardhawi, Schacht Memperjelas apa yang dimaksud dengan metode pemahaman hadits, penting mengawali kajian ini mengetahui terlebih dahulu istilah metode, dan hadits secara semantik. Metode diartikan sebagai “cara yang teratur dan berpikir baik-baik untuk mencapai maksud (dalam ilmu pengetahuan dan sebagainya); cara kerja yang bersistem untuk memudahkan pelaksanaan suatu kegiatan guna mencapai sesuatu yang ditentukan. Dengan demikian, metode pemahaman hadits adalah cara-cara yang diterapkan dalam memahami hadits. Banyak tokoh atau sarjana yang sungguh-sungguh melakukan penelitian terhadap seluruh hadits yang ada, baik yang terdapat dalam kitab-kitab hadits maupun yang tidak ada dalam kitab hadits. Di antara sekian banyak tokoh dan para sarjana hadits baik dari kalangan dunia Islam maupun “ahli” yang sungguh- sungguh mempelajari hadits dari kalangan orientalis (Barat). Dalam artikel singkat ini penulis hanya mengambil tiga tokoh hadits untuk dikaji lebih jauh terkait metode pemahaman mereka terhadap hadis Nabi. Ketiga tokoh tersebut adalah Muhammad al-Ghazali dan Yusuf al-Qardhawi, dan Joseph Schacht. Kata Kunci: Pemahaman Hadits, al-Ghazali, al-Qardhawi, Schacht.